Development Potential of Cities in the Lubelskie Voivodship - Sławomir Dziaduch (Barometr Regionalny)
The goal of the article was the analysis of the development potential of cities in the Lubelskie Voivodship based on endogenous factors. As a main research method the analytical hierarchy process was used. The method solves decision-making problems presented in the form of multi-criteria hierarchical structure. The weights of elements in each level of the hierarchy were obtained as a result of pair-wise comparisons of components constituting development potential. The development potential based on endogenous factors was divided into 5 components: human and social capital, standard of living, economic potential, the local government activity and tourism potential. In terms of development potential Lublin was at first place. The largest city in the region had the best synthetic indices in terms of human and social capital, standard of living and economic potential. The city with the best local government activity was Janów Lubelski, and the highest level of tourism was noted in Kazimierz Dolny. The development potential of cities indicated considerable diversification in groups of administrative functions (cities with powiat status, powiat cities and other cities) as well as territorial division. The lowest development potential was in cities located in the southeast part of the voivodship: Tyszowce, Łaszczów, Szczebrzeszyn, Józefów and also Annopol, Kock and Rejowiec Fabryczny. They were characterized by low transport accessibility, as well as demographic and social problems.